Analysis of the Development of Home Scale Machines in the Food and Beverage Industry: (Case Study in Ready-to-Serve Coffee Sub-Sector) - Cakranegara, Pandu Adi (Journal of Applied Science, Engineering, Technology, and Education, 2021)
Indonesia is a country experiencing demographic growth, especially in the productive age. This growth has several consequences, among others, from income and consumption levels. The increase in the people's standard of living affects various industries, including the food and beverage industry. Apart from macroeconomic and demographic factors, technological factors play an essential role in increasing production. In this case, the availability of coffee machines on a home scale. This machine's existence enables small businesses to start their coffee cafe businesses to compete with large coffee companies. This research uses existing analytical tools between market potential analysis and boarding house structure analysis. This analysis found that there was a decrease in the barrier to entry to the ready-to-serve coffee industry. As a consequence, there are vast opportunities for small businesses to start a business using home-scale machines. This study explains the phenomenon of the rapid development of small-scale coffee in Indonesia in recent years.